OCORRÊNCIA DE LESÕES EM CARCAÇAS BOVINAS E SUAS PERDAS ECONÔMICAS - PIAZZON, Cleiton José; OLIVEIRA, Dalton Mendes; NUNES, ris Luana de Castro; BACHES, Bruna; ESCOBAR, Loraine Saldanha (ANAIS DO ENIC, 2017)
-